New Normal Workplace during the Covid-19 Pandemic in Indonesia - Sugiarto Sumas (Jurnal Bina Ketenagakerjaan, 2021)
The Corona virus (Covid-19) outbreak in Indonesia and large-scale social restriction (PSBB) policies in several regions in Indonesia have had an impact on social interactions, such as changes in people's behavior patterns in socializing, working, shopping and worshiping. The situation, which is not yet known when it will be finished, raises new awareness about the need to adapt to the Covid-19 pandemic. Here, health protocols are followed and life activities return to normal. This study aims to analyze the economic impact of Covid-19 and PSBB in Indonesia, cases of workplace health protocols and new normal policies that functioned during the Covid-19 pandemic in Indonesia. The research method uses a case study approach from John W Creswell to obtain learning about the situations and conditions of the cases referred to. The conclusions of this study are: Covid-19 and PSBB in some parts of Indonesia caused the Indonesian economy to contract in the second quarter of 2020 by 5.32% (Year-on-Year), workers who lost their jobs or lost income at least 2.1 million people, community incomes in the PSBB area have decreased, and health protocols have not been fully implemented and threaten the emergence of new clusters of Covid-19 transmission. The study also identified that the government had developed new normal policy guidelines for employment during the Covid-19 pandemic in Indonesia, and suggested that labor inspections should be firmer and more intensive.